Flavor characterization of six white wines from Xinjiang: Physicochemical property, antioxidant activity, and volatile compounds analysis - Chunyan Li; Xilei Pu; Piping Ye; Qingquan Fu; Yuxuan Zhou; Xin Zhou; Xuewei Shi; Bin Wang (Journal of Agriculture and Food Research)
Wine flavors encompass distinct varietal, fermentation, and aging aromas, with grape variety and terroir playing a crucial role in shaping the variations in wine's aroma. The distinct geographical and climatic conditions in Xinjiang have created a unique terroir. To assess the flavor characteristics of white wines from Xinjiang, we investigated the physicochemical properties, organic acids, phenolic compounds, antioxidant activity, and aroma profiles of Chardonnay (CDW), Riesling (RLW), Gewurztraminer (GTW), Italian Riesling (IRW), Chenin Blanc (CBW), and Ecolly wines (ELW) using HPLC and HS-SPME-GC-MS techniques. The results showed that malic acid and tartaric acid were the dominant organic acids, while quercetin, rutin, and neochlorogenic acid were the most important phenolic compounds in white grapes and the wines. Among them, quercetin, neochlorogenic acid, coumaric acid, and gallic acid contributed substantially to the antioxidant activity in vitro. A total of 64 aromatic compounds were identified in white grapes, while 73 aromatic compounds were identified in the wines. Alcohols (especially isoamylalcohol and phenethyl alcohol) and esters (including ethyl caprylate and phenethyl acetate) were the main volatile compounds, and floral and fruity were typical aromas in white wines. Additionally, aldehydes and other esters may contribute to the fruity and floral flavor formation in the wines from Xinjiang, with β-damascenone potentially playing an indirect role in floral flavor formation. This study provides a theoretical foundation for enhancing the quality of white wine production in Xinjiang.